PENGARUH KEPEMILIKAN INDIVIDUAL, KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN ASING TERHADAP KEBIJAKAN PEMBAYARAN DIVIDEN (STUDI KASUS PADA SEKTOR NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Lia Dariani; Nurhalis Nurhalis (Jurnal Manajemen Inovasi, 2020)
This study aims to examine the effect of individual ownership, institutional ownership and foreign ownership on dividend payment policies that are proxied by the Dividend Payout Ratio (DPR). The sample in this study used a purposive sampling technique that is based on certain criteria. According a sample of 20 non-financial sector companies was listed on the Indonesia Stock Exchange during 2012 to 2017 and analyzed using multiple linear regression methods through Eviews 9 software. The results showed that: (1) individual ownership had a significant negative effect on dividend payment policies. (2) institutional ownership has a significant positive effect on dividend payment policy (3) foreign ownership has a significant positive effect on dividend payment policy.